2008
DOI: 10.1002/pits.20308
|View full text |Cite
|
Sign up to set email alerts
|

Relations among school connectedness, hope, life satisfaction, and bully victimization

Abstract: This study investigates the role of school connectedness in mediating the relation between students' sense of hope and life satisfaction for three groups: Bullied Victims, Peer Victims, and Nonvictims. Students in grades 5 to 12 (N = 866) completed the California Bully/Victim Scale, School Connectedness Scale, Children's Hope Scale, and Students' Life Satisfaction Scale. Multigroup latent mean analysis revealed significant group mean differences in hope, school connectedness, and life satisfaction, supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
85
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 50 publications
11
85
1
8
Order By: Relevance
“…This finding, in combination with those for mental health, suggests that entry into a new college environment and social arena might provide an opportunity for students with histories of bully victimization to experience resilience through the formation of new supportive relationships. In contrast to studies of childhood bullying that find that child victims of bullying report lack of engagement in school 32 and weaker peer relationships in general, 33 our results suggests that previously bullied youth might be hopeful about their college experience. Part of this might be explained by college students having more control over both with whom they interact and the settings in which they study and socialize on college campuses, in contrast to K-12 settings in which students are required to be in the same building all day.…”
Section: Vol 62 November/december 2014 557contrasting
confidence: 55%
“…This finding, in combination with those for mental health, suggests that entry into a new college environment and social arena might provide an opportunity for students with histories of bully victimization to experience resilience through the formation of new supportive relationships. In contrast to studies of childhood bullying that find that child victims of bullying report lack of engagement in school 32 and weaker peer relationships in general, 33 our results suggests that previously bullied youth might be hopeful about their college experience. Part of this might be explained by college students having more control over both with whom they interact and the settings in which they study and socialize on college campuses, in contrast to K-12 settings in which students are required to be in the same building all day.…”
Section: Vol 62 November/december 2014 557contrasting
confidence: 55%
“…Bullying literature have consistently revealed that students with lower level of school connectedness due to negative school environment are prone to bullying and peer victimization (Glew et al 2005;Skues et al 2005;You et al 2008;Young 2004). For sexual minority students, much of homophobic bullying also occurs within the school setting (Russell et al 2001;Ryan and Rivers 2003) where they frequently hear homophobic epithets and experience verbal and physical assault (Kosciw and Cullen 2002;Peters 2003).…”
Section: Microsystem Levelmentioning
confidence: 98%
“…It follows that victims would report a more negative sense of school climate, bonding, and engagement. Indeed, victims in elementary, middle, and high school reported lower school connectedness [45] and higher school dissatisfaction [46] than youth not involved in bullying. However, in another study of 11,033 sixth through tenth graders, there were no significant differences between victims of traditional bullying and non-involved youth in terms of school satisfaction [47], indicating the need for further research.…”
Section: Introductionmentioning
confidence: 99%